Concise encyclopedia of chemical technology (Wiley, 1985)
As a reference work of par excellence. It stands supreme in the field of chemical technology... " -- The Chemical Engineer " Libraries that can afford the investment ... would be well advised to make room for this valuable source." -- Journal of Medicinal Chemistry --This text refers to an out of print or unavailable edition of this title.